Optimalisasi Lingkungan Pendidikan Islam: Strategi Holistik untuk Membentuk Generasi Muslim Berintegritas di Era Global - Aput, Aisyah Rahayu; Fedya Jelila; Gusmaneli (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
Islamic education has a strategic mission to produce individuals who not only excel in science, but also have strong faith, noble morals, and the ability to adapt to global dynamics. The educational environment, as an ecosystem that shapes children’s development, is the main foundation in realizing this goal. This article aims to elaborate on the concept of the Islamic educational environment in depth, classify its types (prenatal, family, school, and community), and analyze formal, non-formal, and informal education pathways as mutually supportive approaches. With an interdisciplinary literature review approach, this article also explores the challenges of globalization, the impact of digital technologies, and opportunities to integrate Islamic education with 21st century skills. Case studies from various countries and strategic recommendations were presented to strengthen the implementation of Islamic education in a global context. This article emphasizes the importance of synergy between environments to produce a generation of Muslims who have integrity, are competitive, and are able to contribute positively in a multicultural society.